Rwanda : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission to assist Rwandan authorities in compiling annual government finance statistics (GFS) for the general government for FY2015/16 and high-frequency GFS for the budgetary central government and central government. It was observed that the annual GFS compilation is on track and even exceeding the expectations. The compilation of high frequency data should now be the focus of the authorities' efforts. Quarterly Central Government data are expected to be compiled within 60 days for FY2017/18. Monthly BCG data are already compiled within 30 days from end of the period. In both cases, the Rwandan authorities have made some initial progress.